2016
DOI: 10.1136/bmjopen-2015-010354
|View full text |Cite
|
Sign up to set email alerts
|

‘Why should I worry, since I have healthy feet?’ A qualitative study exploring barriers to use of footwear among rural community members in northern Ethiopia

Abstract: ObjectiveTo explore the influence of personal, cultural and socioeconomic factors related to footwear use and non-use in northern Ethiopia.DesignA qualitative study was conducted using focus group discussions and in-depth individual interviews. Data were collected using semistructured interview guides.SettingThe study was conducted in East and West Gojjam Zones, Amhara region, northwest Ethiopia.ParticipantsA total of 91 individuals from 4 target groups participated in individual and group interviews: (1) non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
(26 reference statements)
5
24
0
Order By: Relevance
“…Barefoot exposure to soil was also raised by children as a cause of podoconiosis though the role of mineral particles in the soil was mentioned infrequently. This is congruent with previous studies which reported poor knowledge of adult community members about mineral particles in the soil as a causal agent of podoconiosis [ 8 10 , 12 , 43 , 44 ]. Regarding preventive measures, children were well aware of the importance of footwear and foot hygiene.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Barefoot exposure to soil was also raised by children as a cause of podoconiosis though the role of mineral particles in the soil was mentioned infrequently. This is congruent with previous studies which reported poor knowledge of adult community members about mineral particles in the soil as a causal agent of podoconiosis [ 8 10 , 12 , 43 , 44 ]. Regarding preventive measures, children were well aware of the importance of footwear and foot hygiene.…”
Section: Discussionsupporting
confidence: 92%
“…Others associated the risk of getting podoconiosis with bad luck or predisposition, which may also limit their motivation to engage in or maintain preventive action. Such a perception was also reported as common among adults in podoconiosis-endemic communities and acted as a barrier to preventive actions against podoconiosis [ 11 , 12 ]. As children associate their perception of susceptibility to podoconiosis with exposure to poison in the soil, and contact with and insults against affected people, they may consider their exposure to these risk factors beyond their control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, studies 33 of lymphoedema management in patients with lymphatic filariasis have not disaggregated data by sex so it is difficult to contextualise this finding. Observational studies14, 36 among people with podoconiosis suggest that men have more access to shoes, and are more likely to own a pair. In the general population, men are more likely to be found wearing shoes at interview 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A well-documented example is trachoma, where female caregivers come into more frequent contact with infected children than male caregivers and are thus more likely to become infected themselves [5,11]. In the case of podoconiosis, women have been found to be more at risk of acquiring the disease because they are less likely to own or wear shoes, reflecting cultural traditions and because available shoes were perceived to be more suitable for men [12,13]. Other studies have remarked on the underestimation and underreporting of NTDs in women, specifically schistosomiasis and lymphatic filariasis (LF), as diagnosis of these diseases can require women to comply with activities that are perceived as culturally inappropriate or taboo, such as providing a urine or stool sample or allowing intimate physical examination [14,15].…”
Section: Introductionmentioning
confidence: 99%